A new look at cognitive functioning in pediatric MS. (January 2023) - Krupp, Lauren B; Waubant, Emmanuelle; Waltz, Michael; Casper, T Charles; Belman, Anita; Wheeler, Yolanda; Ness, Jayne; Graves, Jennifer; Gorman, Mark; Benson, Leslie; Mar, Soe; Goyal, Manu; et al.
Objective: Cognitive involvement in pediatric multiple sclerosis (MS) relative to adult MS is less defined. This study advances our understanding by measuring cognitive performances in pediatric MS, adult MS, and pediatric healthy controls. Methods: Consecutive relapsing pediatric MS participants from the United States Network of Pediatric MS Centers were compared with pediatric healthy controls and adults with relapsing MS. Participants were compared on two screening batteries: the Brief International Cognitive Assessment for MS and the Cogstate Brief Battery. Results were transformed to age-normative z scores. Results: The pediatric groups (MS vs. Healthy Controls) did not differ on either battery's composite mean score or individual test scores ( p s > 0.32), nor in the proportions impaired on either battery, Brief International Cognitive Assessment for MS (26% vs. 24%, p = 0.83); Cogstate Brief Battery (26% vs. 32%, p = 0.41). The pediatric versus adult MS group even after controlling for differences in disease duration performed better on the Brief International Cognition Assessment for MS composite ( p = 0.03), Symbol Digit Modalities Test ( p = 0.02), Rey Auditory Verbal Learning Test ( p = 0.01), and Cogstate choice reaction time ( p < 0.001). Conclusion: Pediatric MS patients do not differ from healthy pediatric controls on cognitive screens but perform better than adults with MS.